Sistem Penyiraman Otomatis Terdistribusi untuk Tanaman Melon Madu Berdasarkan Usia dan Kebutuhan Nutrisi - Utama, Jana; Herdiana, Budi; Adhari , Febryan (Universitas Djuanda, 2024)
Regular watering and with the right portion are very important in melon cultivation. The current melon fruit watering system is still done by turning the water tap on the watering pipe block to flow the water. Therefore, there needs to be an application of technology that can help melon farmers in the watering process. Although many researchers have developed automatic watering models, some have even used IoT technology. However, this study has not considered the need for watering based on the age of the melon plant itself. In fact, this automatic watering system based on the age of the melon plant is what melon farmers need, so that the melon plants grow well and produce quality fruit. This study aims to develop a distributed automatic watering system based on the age of the plant and nutritional needs. The methods used include the integration of electronic instrumentation technology and distributed automatic control to provide the right watering process. The results of the study showed that this system is effective in optimizing the watering process so that nutrients can be absorbed properly. With this system, the level of fruit sweetness at harvest can reach 17 brix, and the size of the honey melon produced can reach 1.2 kg. In conclusion, this distributed automatic watering system is a smart solution to optimize the growth and yield of melon plants.